ATTITUDES ABOUT HONOUR KILLING AMONG MEN AND WOMEN -PERSPECTIVE FROM ISLAMABAD - Shaikh, Masood Ali; Shaikh, Irshad Ali; Kamal, Anila; Masood, Sobia (Journal of Ayub Medical College Abbottabad, 2010)
Background: The concept of honour has cultural, social and moral underpinnings that determine its expression and perseveration. Women are viewed as the bearers of family honour with chastity equated with abstinence from premarital or extramarital relationships and obeying norms determined and dictated by traditions and societies. The objective of this study was to determine the opinions of men and women pertaining to killing in the name of and saving one’s honour. Methods: A cross-sectional survey with convenience sampling was conducted among the 18 years and older (range 18-71) men and women. Respondents were approached in markets, bus-stops, hospitals, and various other public places in Islamabad from April 12th to June 27th 2006. A structured, interviewer-administered, and pretested questionnaire was used with both open and close-ended questions on demographics and attitudes about honour killing based on a vignette that was slowly read out in Urdu, in a neutral and judgmentfree tone of voice to potential respondents. Responses to close-ended questions based on the vignette provided, and pattern among men and women were compared using Pearson Chi-square test to determine associations between the dichotomous variables and gender, while responses to one openended question were summarised based on the observed similarities and bivariate associations with gender were determined. Results: We approached 630 conveniently selected individuals at various public places in the city of Islamabad. Six hundred and one agreed to participate and completed the questionnaire, i.e., the response rate was 95.4%. Three hundred and seven respondents were male (51.1%), and 294 (48.9%) were females. Three hundred forty-three 343 (57.1%) respondents believed that the man in the vignette did the right thing by killing his wife upon finding her in bed with another man. Divorcing one’s wife rather than resorting to killings, after having found her with another man was approved by 220 (36.6%) respondents, while the rest answered as ’˜don’t know’. Conclusion: Majority of men as well as women considered it justifiable and acceptable to kill one’s wife as a mean to save one’s honour. The most significant finding was the fact that overwhelming number of men and women did not believe in either forgiveness or divorcing one’s wife who has engaged in extramarital sexual relationship. Keywords: Honour killing, Women, Opinion